The attitude of teachers towards integrative education - Samsonienė, Laimutė; Adomaitienė, Rūta (Socialinė teorija, empirija, politika ir praktika, 2003)
The attitude towards integrative education is explored in the paper. The survey method was used for data collection. The 270 teachers were participating in the research from nine schools in Vilnius. The data analyses revealed that schoolteachers are not prepared to teach disable children; also, they do not want to teach children with mental disability. The authors suggest installing the curse of special education into curricula of educators, to organise the seminars and refresher course.